Exploring the adoption of virtual work: the role of virtual work self-efficacy and virtual work climate. Issue 17 (25th September 2022) - Adamovic, Mladen; Gahan, Peter; Olsen, Jesse; Gulyas, Andre; Shallcross, David; Mendoza, Antonette
Abstract: Previous research has shown that virtual work provides benefits to individual employees (e.g. less stress, higher job satisfaction, and higher productivity), the organization (e.g. lower real estate costs and higher commitment and performance) and, potentially, society at large (less traffic, less pollution, and lower healthcare costs through reduced stress and work-family conflict). To realize the potential benefits associated with virtual work, many organizations have introduced new policies to enable employees to work virtually. However, research evidence and media reports indicate that many employees are hesitant to utilize the opportunity to work virtually. To better understand this gap between formal organizational policies and actual adoption, we investigate the predictors and conditions of virtual work adoption. Drawing on Lewin's field theory and Bandura's social cognitive theory, we examine the extent to which virtual work self-efficacy, virtual work climate, and their interaction predict individual adoption of virtual work arrangements. To test our hypotheses, we conducted a survey study of 256 employees from a multinational information technology company. Our results suggest that an effective virtual work climate encourages employees with low virtual work self-efficacy to engage in more virtual work.